Diagnosing Oncocytoma by Core Needle Biopsy: A Single-Center Experience - Chen Mayer; Yasmin Abu-Ghanem; Zohar A. Dotan; Iris Barshack; Eddie Fridman (Advances in Urology)
Background. Oncocytoma is one of the most common benign kidney tumors, accounting for 3–7% of all solid renal masses. Diagnosing oncocytomas using renal biopsy remains a controversy in the uro-pathologic community. With the increasing use of biopsies for assessment of renal lesions, reaching this pathologically benign diagnosis may prevent further surgical measures and have significant clinical benefit. Objective. To demonstrate our center’s results using renal biopsy to diagnose oncocytomas and to suggest that this diagnosis can be made with high success rates. Design, Setting, and Participants. From our center’s database, we retrospectively identified and retrieved all cases of oncocytoma diagnosed between the years 2011 and 2020 by renal biopsy. Medical records of those patients were then reviewed to view follow-up meetings and imaging of the lesions biopsied. Outcome Measurements and Statistical Analysis. In 21 biopsies performed on 19 patients, diagnosis was supported by subsequent follow-up averaging at 3.44 years per patient. Results and Limitations. The lesions exhibited benign behavior during follow-up after biopsy, consistent with the diagnosis of oncocytoma. Conclusions. Our study demonstrates that with good patient selection and proficient cooperation between urologists, radiologists and dedicated uro-pathologists, correctly diagnosing oncocytomas using RCB is a viable task. Patient Summary. Oncocytomas are benign lesions of the kidney. In our study, we reviewed all cases of oncocytomas pathologically diagnosed using renal biopsy from our center’s database. We found that in subsequent follow-up later to biopsy, the lesions displayed benign behavior consistent with oncocytoma. The use of percutaneous biopsies to reach this diagnosis could save patients more extensive surgeries.